Analysis of Intestinal Metabolites in SR−B1 Knockout Mice via Ultra−Performance Liquid Chromatography Quadrupole Time−of−Flight Mass Spectrometry - Qijun Chen; Lixue Wang; Jinlong Chen; Hui Song; Wen Xing; Ziqian Wang; Xueying Song; Hua Yang; Wenhua Zhao (Molecules, 2023)
Scavenger receptor class B type 1 (SR−B1), a multiligand membrane receptor, is expressed in a gradient along the gastrocolic axis. SR−B1 deficiency enhances lymphocyte proliferation and elevates inflammatory cytokine production in macrophages. However, whether SR−B1 affects intestinal metabolites is unclear. In this study, we detected metabolite changes in the intestinal tissue of SR−B1−/− mice, including amino acids and neurotransmitters, by ultra−performance liquid chromatography quadrupole time−of−flight mass spectrometry (UHPLC−Q−TOF/MS) and HPLC. We found that SR−B1−/− mice exhibited changes in intestinal lipid metabolites and metabolic pathways, including the glycerophospholipid, sphingolipid, linoleic acid, taurine, and hypotaurine metabolic pathways. SR−B1 deficiency influenced the contents of amino acids and neurotransmitters in all parts of the intestine; the contents of leucine (LEU), phenylalanine (PHE), tryptophan (TRP), and tyrosine (TYR) were affected in all parts of the intestine; and the contents of 3,4−dihydroxyphenylacetic acid (DOPAC) and dopamine (DA) were significantly decreased in both the colon and rectum. In summary, SR−B1 deficiency regulated intestinal lipids, amino acids, and neurotransmitter metabolism in mice.